PENGARUH PENDIDIKAN KESEHATAN TENTANG OHO TERHADAP TINGKAT PENGETAHUAN DAN KEPATUHAN MINUM OBAT PASIEN DIABETES MELITUS PADA ERA PANDEMI COVID-19 - Purwandari, Kristiana Puji; Wulandari, Isnur (Akademi Keperawatan Giri Satria Husada Wonogiri, 2023)
ABSTRACTBackground: The Indonesian Ministry of Health, October 13, 2020 edition (Covid-19 Task Force) shows data from 1488 patients, about 34.5% of patients with DM (Diabetes Mellitus). Then, of the 1488 patients who died due to Covid-19, 11.6% of them suffered from DM. Health education about OHO aims to provide information to DM patients about oral hypoglycemic drugs, so as to increase patient knowledge and compliance. Based on this, a study was conducted to determine the effect of health education on OHO and adherence to medication for Diabetes Mellitus patients during the Covid-19 pandemic. Research Methods: This research is a type of qualitative descriptive research with a case study research approach (case study). The population in this study were people with Diabetes Mellitus in Slogohimo District, precisely in Randusari and Setren Villages, Wonogiri Regency with a sample of 5 respondents. Research Results: Results (pre-test) knowledge level: 3 respondents in the low category (60%), 2 respondents in the medium category (40%). Results (pretest) level of adherence to medication: 3 respondents in the low category (60%), 2 respondents in the moderate category (40%). The results (post-test) of the knowledge level of 5 respondents in the high category (100%). The results (post-test) of the level of adherence to taking medication are 4 respondents in the high category (80%) and 2 respondents in the moderate category (20%). Conclusion: The five respondents experienced an increase in the level of knowledge and adherence to taking medication after being given health education about DM and OHO. Thus, the provision of OHO health education (Oral Hypoglycemic Drugs) affects the level of knowledge and adherence to taking medication for Diabetes Mellitus (DM) patients during the COVID-19 pandemic. ABSTRAKLatar Belakang : Kementerian Kesehatan RI edisi 13 Oktober 2020 (Satgas Covid-19) menunjukan data dari 1488 pasien, sekitar 34,5% pasien penderita DM (Diabetes Melitus). Kemudian, dari 1488 pasien yang meninggal dunia akibat Covid-19, didapatkan 11,6% dari mereka menderita DM. Pendidikan kesehatan tentang OHO bertujuan untuk memberikan informasi kepada pasien DM mengenai obat hipoglikemik oral, sehingga mampu meningkatkan pengetahuan dan kepatuhan pasien. Berdasarkan hal tersebut dilakukan penelitian untuk mengetahui pengaruh pendidikan kesehatan tentang OHO dan kepatuhan minum obat pasien Diabetes Melitus di masa pandemi Covid-19. Metode Penelitian : Penelitian ini merupakan jenis penelitian deskriptif kualitatif dengan pendekatan case study research (studi kasus). Populasi pada penelitian ini adalah penderita Diabetes Melitus di Kecamatan Slogohimo tepatnya di Desa Randusari dan Setren, Kabupaten Wonogiri dengan sampel 5 responden. Hasil Penelitian : Hasil (pre-test) tingkat pengetahuan : 3 responden kategori rendah (60%), 2 responden kategori sedang (40%). Hasil (pre-test) tingkat kepatuhan minum obat : 3 responden kategori rendah (60%), 2 responden kategori sedang (40%). Hasil (post-test) tingkat pengetahuan 5 responden kategori tinggi (100%). Hasil (post-test) tingkat kepatuhan minum obat 4 responden kategori tinggi (80%) dan 2 Responden kategori sedang (20%). Kesimpulan : Kelima responden mengalami peningkatan tingkat pengetahuan dan kepatuhan minum obat setelah diberikan pendidikan kesehatan tentang DM dan OHO. Sehingga, pemberian pendidikan kesehatan OHO (Obat Hipoglikemik Oral) berpengaruh terhadap tingkat pengetahuan dan kepatuhan minum obat pasien Diabetes Melitus (DM) di masa pandemi covid-19.